Examining Caregiver Outcomes in the CONNECT Intervention for Patients With Advanced Cancer - Semere, Wagahta; Althouse, Andrew D.; Arnold, Robert; White, Douglas; Smith, Thomas J.; Chu, Edward; Rosenzweig, Margaret Q.; Schenker, Yael (Journal of pain and symptom management, 2023)
Palliative care offers patient and family centered approaches that may mitigate risk of caregiver burden and poor mood. To determine whether a palliative care intervention (CONNECT) improved burden, mood, and self-efficacy among caregivers of patients with advanced cancer. In this cluster randomized trial, patients and their caregivers were recruited from 17 Oncology clinics in Pennsylvania. Participants attended nurse-led monthly visits, addressing patient symptoms, goals of care, and advance care planning. At baseline and three months, we measured caregiver burden using Zarit Burden Interview (ZBI-12; range 0–48), caregiver anxiety and depression using Hospital Anxiety and Depression Scales (HADS-A, range 0–21; HADS-D, range 0–21). We measured caregiver self-efficacy at three months using Caregiver Inventory (CGI; range 0–189). We enrolled 441 caregivers and 381 completed three-month assessments. We found no significant differences in caregiver burden (adjusted mean difference -0.39; 95% CI -1.07–0.29, P = 0.90), depression (adjusted mean difference -0.22, 95% CI -0.97–0.55, P = 0.26), or anxiety (adjusted mean difference 0.09; 95% CI -1.25–1.43, P = 0.58), between the intervention and standard care at three months. Caregiver self-efficacy was higher at three months in the intervention compared to standard care (adjusted mean difference 9.36; 95% CI 0.95–17.77, P = 0.030). Caregivers in CONNECT did not experience improved burden or mood, however, they reported higher self-efficacy compared to caregivers receiving standard care. This study highlights the need for strategies to optimize caregiver outcomes in palliative care interventions.